2016
DOI: 10.1002/2015gl067327
|View full text |Cite
|
Sign up to set email alerts
|

Do MODIS‐defined dust sources have a geomorphological signature?

Abstract: The preferential dust source (PDS) scheme enables large‐scale mapping of geomorphology in terms of importance for dust emissions but has not been independently tested other than at local scales. We examine the PDS qualitative conceptual model of surface emissivity alongside a quantitative measurement of dust loading from Moderate Resolution Imaging Spectroradiometer (MODIS) Deep Blue Collection 6 for the Chihuahuan Desert. The predicted ranked importance of each geomorphic type for dust emissions is compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 37 publications
3
54
0
Order By: Relevance
“…MISR-derived and SeaWiFS-derived DOD were not further utilized because of the limited amount of retrievals and much smaller values and variance in comparison to MODIS-derived one, as found above (Figures 7 and 8). AOD retrievals with all quality flags were used following the recommendation by Baddock et al [44] to derive the dust occurrence numbers, because the quality flag is not well marked over desert regions where a larger standard deviation is always found [4]. Consistent to Baddock et al [44], a threshold DODt = 0.2 was also applied in the present study to count the dust occurrence numbers.…”
Section: Dust Occurrencesmentioning
confidence: 99%
See 1 more Smart Citation
“…MISR-derived and SeaWiFS-derived DOD were not further utilized because of the limited amount of retrievals and much smaller values and variance in comparison to MODIS-derived one, as found above (Figures 7 and 8). AOD retrievals with all quality flags were used following the recommendation by Baddock et al [44] to derive the dust occurrence numbers, because the quality flag is not well marked over desert regions where a larger standard deviation is always found [4]. Consistent to Baddock et al [44], a threshold DODt = 0.2 was also applied in the present study to count the dust occurrence numbers.…”
Section: Dust Occurrencesmentioning
confidence: 99%
“…AOD retrievals with all quality flags were used following the recommendation by Baddock et al [44] to derive the dust occurrence numbers, because the quality flag is not well marked over desert regions where a larger standard deviation is always found [4]. Consistent to Baddock et al [44], a threshold DODt = 0.2 was also applied in the present study to count the dust occurrence numbers. To avoid the contamination of the use of a threshold constant on the results, a series of threshold values close to 0.2 was applied to the dust event selecting procedure to yield a more robust conclusion.…”
Section: Dust Occurrencesmentioning
confidence: 99%
“…A surface erodibility factor is typically used in dust models to constrain the observed spatial heterogeneity of emissions (Zender et al, ). Several dust emission mapping schemes at the landscape scale have attempted to account for erodibility as a regulator of emission potential for use in dust models (e.g., Ashpole & Washington, ; Baddock et al, ; Bullard et al, ; Parajuli et al, ; Parajuli & Zender, ). The erodibility factor has typically been based on various physical assumptions of the influence of geomorphology, topography, and hydrology on dust emission (Ginoux et al, ; Zender et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of dust emission processes has been greatly enhanced by studies that have identified dust sources on global, regional, and landscape scales through various remote sensing approaches primarily using the Total Ozone Mapping (TOMS) and more recently the MODIS sensors (e.g., Baddock et al, ; Bullard et al, ; Ginoux et al, ; Huang et al, ; Lee et al, ; O'Loingsigh et al, ; Prospero et al, ; Schepanski et al, , ; Vickery et al, ; Washington et al, ). However, a fuller appreciation of the smaller‐scale controls contributing to the variability in dust emission also depends on the improved characterization of dust sources at a sublandform scale.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the attribution of dust generation and flux to different dust‐producing landforms and processes is sometimes not straightforward. As a primary reason, spatial resolution of observations, especially from space‐based platforms, such as Moderate Resolution Imaging Spectroradiometer (MODIS), is often too crude to recognize source areas even when, and sometimes because, plumes are dense, notwithstanding recent analyses and progress (Baddock et al, , ; Bullard et al, ; Schepanski et al, ). Successful estimates of AOD (atmospheric optical depth) on a global scale have been derived from Collection 6 MODIS data, the Dark Target, and Deep Blue products in particular (Hsu et al, ; Ridley et al, ).…”
Section: Introductionmentioning
confidence: 99%